Bandwidth-efficient 5G optical fronthaul based on carrier aggregation - Loureiro, Pedro Emanuel Amaral (2021)
With the introduction of the next generation 5G systems, an unprecedented bit rate demand for optical transport infrastructure is expected, in addition to the need to ensure low costs, low power consumption, and low latency. With the current analog radio over fiber approach, high spectral efficiency is achieved, therefore, this is a fundamental technology for the next generation fronthaul system. This thesis addresses the possibility of using an analog radio-over-fiber system in a fronthaul of a Cloud Radio Access Network, avoiding the well-known bandwidth multiplication issue associated with the digitization of radio signals. Using a low-cost directly modulated laser and a standard PIN, we have experimentally demonstrated how to obtain a 5G-compliant EVM on all component carriers by optimizing power and bit loading between component carriers.